Influência do ambiente em características relacionadas ao florescimento da mamoneira - Da Lara, Ana C.C. [UNESP]; Zanotto, Maurício Dutra [UNESP]; Okita, Cristiane H. [UNESP] (Revista Brasileira de Ciencias Agrarias, 2012)
The castor bean tree flowering is complex due to the variations that occur in the sexual expression of the racemes depending on the genetic material and the environment. In order to evaluate the influence of the environment on the characteristics related to flowering in castor bean strains, and to study the potential of strains in hybrids production, eight strains were evaluated in two production sites: Botucatu (SP) and São Manuel (SP), Brazil, during two periods: 2008 and 2009. The following characteristics were evaluated: number of days for average flowering; sexual expression of the primary and secondary racemes; number of nodes until primary inflorescence; and raceme length. Regarding production sites, there were significant effects on the interaction between sites x strains for the characteristics number of days to average inflorescence and number of nodes until primary inflorescence, as well as in the joint analysis for the years. Most strains showed high frequency of plants with female primary racemes in both locations and periods, and, therefore, have a great potential for hybrids production.
Influence of the environment on characteristics related to castor bean trees flowering
Keywords: Hybrids production; Ricinus communis L.; Sexual expression; Ricinus communis